Linking a genome‐wide association study signal to a LRRK2 coding variant in Parkinson's disease. Issue 4 (21st December 2015) - Foo, Jia Nee; Chung, Sun Ju; Tan, Louis C.; Liany, Herty; Ryu, Ho‐Sung; Hong, Myunghee; Koh, Tat Hung; Irwan, Ishak D.; Au, Wing‐Lok; Prakash, Kumar‐M.; Aung, Tin; Cheng, Ching‐Yu; et al.
ABSTRACT: Background: Genome‐wide association studies have identified several loci associated with Parkinson's disease (PD). Whole‐exome sequencing detects rare coding variants, but their links with PD genome‐wide association study loci are unknown. Our objective was to investigate whether nonsynonymous variants in LRRK2 can explain associations at the PD‐associated locus tagged by rs1994090. Methods: We sequenced all coding exons of LRRK2 in 453 East Asian samples and evaluated linkage disequilibrium between each nonsynonymous variant and rs1994090. We then tested selected variants and haplotypes for association with PD in 13, 581 East Asian samples. Results: Of all the nonsynonymous variants, only p.Gly2385Arg was in moderate linkage disequilibrium with rs1994090 and was observed on haplotypes tagged by the rs1994090‐C risk allele. Conditional analyses showed that associations at these 2 variants are not independent. Conclusions: LRRK2 p.Gly2385Arg can explain most if not all of the PD association at rs1994090 in East Asians, but other nonsynonymous variants are independent. © 2015 International Parkinson and Movement Disorder Society